The Challenge in Differentiating Acute Fatty Liver of Pregnancy from Other Hepatic Disorders in Parturient Women – A Case Report - Santoso, Tiffanie Almas; Andrea, Demirel; Setiawan, Dani (Indonesian Journal of Obstetrics & Gynecology Science, 2024)
Introduction: Liver disorder during pregnancy can arise from pregnancy-related factors or other underlying causes. One significant example is Acute Fatty Liver of Pregnancy (AFLP), a rare but life-threatening obstetric emergency that typically occurs in the third trimester or early postpartum period. Diagnosis of AFLP is carried out using the Swansea criteria, and its clinical management varies depending on the severity of the condition.Case Illustration: A 23-year-old woman, at 33-34 weeks of gestation in a multifetal pregnancy, presented with abdominal contractions and jaundice. The patient was diagnosed with AFLP using the Swansea criteria, Following the diagnosis, the patient delivered twins and received multidisciplinary care. After seven days of inpatient care, jaundice improved, symptoms resolved, and there were no signs of coagulation disorders.Discussion: AFLP is a rare condition that normally occurs in the third trimester, with risk factors including multiple pregnancies and metabolic disorders. Symptoms can be nonspecific but may lead to acute liver failure, thereby timely diagnosis and management are crucial. Treatment primarily involves prompt delivery and supportive care to manage complications such as hypoglycemia and renal failure.Conclusion: Early identification of AFLP can be challenging due to its similarities with other conditions, but the Swansea criteria can help assess its severity and potential complications for both mothers and fetuses.Tantangan dalam Membedakan Acute Fatty Liver dalam Kehamilan dengan Penyakit Hati Lainnya pada Wanita Parturien – Sebuah Laporan KasusAbstrakPendahuluan: Penyakit hati selama kehamilan dapat berkaitan dengan kehamilan atau memiliki penyebab lain. AFLP, sebuah keadaan darurat obstetri yang langka dan mengancam jiwa yang terjadi pada trimester ketiga atau periode postpartum awal, didiagnosis menggunakan kriteria Swansea dan memerlukan penanganan klinis yang bervariasi karena spektrum keparahannya. Ilustrasi Kasus: Seorang wanita berusia 23 tahun pada usia kehamilan 33 - 34 minggu dengan kehamilan multifetal datang dengan kontraksi abdomen dan jaundice. Pasien terdiagnosis acute fatty liver of pregnancy (AFLP) dengan menggunakan kriteria Swansea. Pasien melahirkan bayi kembar dan menerima perawatan multidisiplin pascasalin. Setelah tujuh hari perawatan rawat inap, jaundicenya membaik, dan gejalanya menghilang, tanpa tanda-tanda gangguan koagulasi. Diskusi: AFLP adalah kondisi langka yang biasanya terjadi pada trimester ketiga, dengan faktor risiko termasuk kehamilan ganda dan gangguan metabolik. Gejalanya tidak spesifik, tetapi dapat menyebabkan gagal hati akut sehingga diagnosis dan penanganan yang tepat waktu sangat penting. Perawatan utamanya melibatkan persalinan yang cepat dan perawatan suportif untuk menangani komplikasi seperti hipoglikemia dan gagal ginjal.Kesimpulan: Identifikasi dini AFLP bisa menjadi tantangan karena kesamaannya dengan kondisi lain, tetapi kriteria Swansea dapat membantu menilai keparahan dan komplikasi potensial bagi ibu dan janin.Kata kunci: Acute Fatty Liver pada Kehamilan; Diagnosis ; Parturien; Penyakit Hati